Evaluating oxidative stress targeting treatments in in vitro models of placental stress relevant to preeclampsia - Afrose, Dinara; Johansen, Matt D.; Nikolic, Valentina; Karadzov Orlic, Natasa; Mikovic, Zeljko; Stefanovic, Milan; Cakic, Zoran; Hansbro, Philip M.; McClements, Lana (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPreeclampsia is a complex pregnancy disorder characterized by the new onset of hypertension and organ dysfunction, often leading to significant maternal and fetal morbidity and mortality. Placental dysfunction is a hallmark feature of preeclampsia, which is often caused by inappropriate trophoblast cell function in association with oxidative stress, inflammation and/or pathological hypoxia. This study explores the role of oxidative stress in trophoblast cell-based models mimicking the preeclamptic placenta and evaluates potential therapeutic strategies targeting these mechanisms.MethodsUric acid (UA) and malondialdehyde (MDA) concentrations were measured in human plasma from women with preeclampsia (n = 24) or normotensive controls (n = 14) using colorimetric assays. Custom-made first trimester trophoblast cell line, ACH-3P, was exposed to various preeclampsia-like stimuli including hypoxia mimetic (dimethyloxalylglycine or DMOG, 1 mM), inflammation (tumour necrosis factor or TNF-α, 10 ng/mL) or mitochondria dysfunction agent, (Rhodamine-6G or Rho-6G, 1 μg/mL), ± aspirin (0.5 mM), metformin (0.5 mM), AD-01 (100 nM) or resveratrol (15 µM), for 48 h. Following treatments, UA/MDA, proliferation (MTT), wound scratch and cytometric bead, assays, were performed.ResultsOverall, MDA plasma concentration was increased in the preeclampsia group compared to healthy controls (p < 0.001) whereas UA showed a trend towards an increase (p = 0.06); when adjusted for differences in gestational age at blood sampling, MDA remained (p < 0.001) whereas UA became (p = 0.03) significantly correlated with preeclampsia. Our 2D first trimester trophoblast cell-based in vitro model of placental stress as observed in preeclampsia, mimicked the increase in UA concentration following treatment with DMOG (p < 0.0001), TNF-α (p < 0.05) or Rho-6G (p < 0.001) whereas MDA cell concentration increased only in the presence of DMOG (p < 0.0001) or Rho-6G (p < 0.001). Metformin was able to abrogate DMOG- (p < 0.01), Rho-6G- (p < 0.0001) or TNF-α- (p < 0.01) induced increase in UA, or DMOG- (p < 0.0001) or TNF-α- (p < 0.05)induced increase in MDA. AD-01 abrogated UA or MDA increase in the presence of TNF-α (p < 0.001) or Rho-6G (p < 0.001)/DMOG (p < 0.0001), respectively. The preeclampsia-like stimuli also mimicked adverse impact on trophoblast cell proliferation, migration and inflammation, most of which were restored with either aspirin, metformin, resveratrol, or AD-01 (p < 0.05).ConclusionOur 2D in vitro models recapitulate the response of the first trimester trophoblast cells to preeclampsia-like stresses, modelling inappropriate placental development, and demonstrate therapeutic potential of repurposed treatments.